Kajian Pustaka Perkembangan Genre Games Dari Masa Ke Masa - Rio Caesar (Journal of Animation and Games Studies, 2015)
In the development of the game world for the past 30 years video games have become an integral part of our culture and even spawned a multimillion dollar industry. Various types of devices are created in line with these developments. Genre (category) in video games are also experiencing rapid development in conjunction with berkembanganya video game itself, in addition to the development of the game genres are also influenced by the rapid development of technology device created. A game does not just fall into a genre, it could be a game included in several genres at once. This paper will discuss the development of the genre of games based on the device that is created in the history of the game from time to time.Keywords: genre, video games, history, gaming devices.AbstrakDalam perkembangan dunia game selama 30 tahun belakangan ini video game sudah menjadi bagian yang tidak terpisahkan dari kebudayaan kita dan bahkan melahirkan industri yang bernilai jutaan dollar. Berbagai jenis perangkat diciptakan seiring dengan perkembangan tersebut. Genre (kategori) dalam video game juga mengalami perkembangan yang pesat bersamaan dengan berkembanganya video game itu sendiri, selain itu perkembangan genre game juga dipengaruhi oleh perkembangan pesat dari teknologi perangkat yang diciptakan. Sebuah game tidak hanya termasuk ke dalam sebuah genre saja, bisa saja sebuah game termasuk dalam beberapa genre sekaligus. Pada paper ini akan dibahas mengenai perkembangan genre game berdasarkan dari perangkat yang yang tercipta dalam sejarah perkembangan game dari masa ke masa.Kata kunci: genre, video game, sejarah, perangkat game.